SKEMA STAGGERED GRID UNTUK SIMULASI PERSAMAAN SWE 2 DIMENSI - Susilo, Panji
In this thesis report, we discuss about the staggered grid scheme for simulation of SWE one-dimensional and two-dimensional. The staggered grid scheme is a scheme which is stable and free from numerical damping error. The stability condition for this scheme is Courant number less than or equal to one. In the simulation using the scheme for 1D SWE, for the case of wave reflected by a closed wall, we obtain an amplification factor 2. Using the analogous staggered scheme for 2D SWE, simulations of wave reflection by hard walls gave the same amplification factor, which is approximately 2. The above results are obtained for various plane wave directions. Finally, we also present a simulation of wave diffraction.